Dormitory Management as an Effort to Improve the Islamic Character of Students Diniyyah Pasia Modern Islamic Boarding School - Nabila Zakiya; Sufyarma M; Sulastri Sulastri (International Journal of Educational Dynamics, 2022)
In the management of an organization or educational institution, Islamic boarding schools are educational institutions that have their characteristics. The hallmark of Islamic boarding schools is the existence of a hut as a temporary residence for female students also called Santriwati has become a hereditary tradition that distinguishes Islamic boarding schools from other education systems. The dormitory for Islamic boarding school is very important because it is a shelter for female students (Santriwati) as well as for studying religious sciences, studying classical books, and imitating the attitudes of Kyai, Ustadzah, and Musyrifah who are in the dormitory. This is by the purpose of education in Islamic boarding schools, namely that students can have good and noble Islamic characters. To achieve the goals of education in Islamic boarding schools, Islamic boarding schools need to manage Islamic boarding schools well so that they can face the currents of globalization. As a place for the cadre of scholars, the development of methodologies and knowledge, an ideal place for the transformation, motivation, and innovation of female students (Santriwati) and Islamic boarding schools are expected to be able to contribute to the formation of the student's Islamic character. In this study, the researcher used a qualitative approach, while the method used was a case study method. The findings obtained from the results of processing and analyzing qualitative data with in-depth observation and interview techniques on the focus of the research "Management of Dormitory as an Effort to Improve the Islamic Character of Students in Diniyyah Pasia Modern Islamic Boarding Schools". In general, the role of the dormitory manager or Musyrifah room carrying out its function as a hostel manager from planning, organizing, implementing, and controlling can improve the Islamic character of female students (Santriwati) both at the stage of moral knowing, moral loving and moral doing.